The Efficiency of Semantic Map Strategy in Female Pupil’s Achievement in the Primary Fifth Class for the Subjects of History and Geography - Hussein Fadhil, Sahar; Hameed Wadi , Hiba; Jassim Mohammed, Wijdan (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to know the efficiency of the semantic map strategy in the fifth primary class female pupil’s achievement in the material of history and geography studies. To verify the research goal and hypotheses, a sample of fifth-grade primary school students was chosen in the Al-Akhtal School for Girls of the General Directorate for Education in Diyala Governorate. The research sample was 722 female students, consisting of two divisions (A and B). Division (A) was chosen to be the experimental group, and the number of students was 37 female students who study the semantic map strategy, whereas division (B) was chosen to be the control group, and the number of female students was 35. The researcher conducted parity in the variables (the age, calculated by month, IQ test, mid-year grades) between them.